Determinants of capital structure: An empirical study on Vietnamese listed firms - Thanh, Le Trung; Huong, Do Mai (Serbian Journal of Management, 2017)
This paper aims to explore the capital structure of listed Vietnamese companies in an updated context of financial development (the recent situation of domestic equity and debt capital market). By applying Random Effect model for panel data, we analyze 05 firm-specific and 01 country-specific determinants of capital structure based on the data set of 228 firms listed on Ho Chi Minh Stock Exchange during the period 2010 – 2014. The results indicated that The Pecking Order theory better explains the financing behaviors of Vietnamese listed firms. Accordingly, although in recent years, Vietnam’s equity market and corporate debt capital market have evolved considerably, the capital structure of Vietnamese companies are still dominated by the use of short-term financing sources. High-growth firms or large-sized firms still rely heavily on external debt rather than equity issuance while State-owned enterprises (SOE) are reported to have positive association with the use of long-term financing sources. This study proposed some recommendations to the policymakers in two dimensions: improving the efficiency and role of capital markets to mitigate the reliance on short-term funds and ensuring that bank finance is allocated on a commercial basis.